Managing records as a key strategic asset for administrative reform in Africa - Wamukoya, Justus Murunga ([s.n.] [S.l.], 1995)
Represents a brief report of some of the recent activities in Africa which have focused on the rehabilitation and development of records and archival systems which are needed to support the current economic and administrative initiatives being undertaken by various governments.